Activated carbon production from spent mushroom substrate for sulfide removal - Muhamad Adib, Rinalto; Nur Syahirah, Mohammad Nor; Muhammad Faiz, Mohamed Ameen; N., Zainol; Sunarti, Abd Rahman (Asian Research Publishing Network (ARPN), 2019)
Agriculture industry in Malaysia has evolved entirely over the last decade due to the advancement in science and technology. Also, Malaysia’s mushroom industry has also shown an upward trend recently. Thus, the increasing of mushroom production in Malaysia also has led to the increasing of mushroom waste such as the spent mushroom substrate (SMS). It is estimated that for 1 kg of mushrooms grown, about 5 kg of SMS is produced. Since the SMS has high potential to be converted into activated carbon (AC) by pyrolysis method and chemical activation, thus this study is crucial to produce the AC derived from the SMS to be used in industrial application especially in the wastewater treatment as the AC has a very excellent adsorption property. Using AC from SMS, 93.7% of sulfide from the industrial wastewater was successfully removed. The optimum condition to produce AS was at the heating temperature of 515°C and heating time of 106 min.